Band gap engineering of nanostructure Cu doped CdO films - Gupta, R. K.; Yakuphanoğlu, Fahrettin; Amanullah, F. M. (Elsevier, 2011)
Nanostructured Cu doped CdO films were fabricated using the sol-gel spin coating technique. Surface morphology and particle size of the films were studied by atomic force microscopy. Atomic force microscopy study revealed that the particle size of the films is a nanometers and particle size is decreased with increase in Cu doping levels. The band gap of the CdO film was found to decrease by Cu doping. Among the Cu doped CdO films, the band gap was observed to increase with increase in Cu doping level. The effect of particle size on the widening of the band gap was observed for Cu doped films. The observed increase in the band gap is explained on the basis of quantum size effects. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Oxide Thin-Films; Optical-Properties; Electrical-Properties; Highly Transparent; Sno2